Pendampingan Penyusunan Laporan Keuangan UMKM Rumput Laut Ora Food - Maria Regina Nansi; Ani Purwanti; Mareta Hadi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Assistance in Financial Preparation of Ora Food Seaweed MSMEs is carried out in order to provide understanding to MSME owners and sustainability in business operational practices. Successful preparation of financial reports consistently will create a financial atmosphere that supports business success. This community service is packaged in training and assistance in simple financial preparation by implementing a simple accounting system. Post-training follow-up assistance is provided in order to cultivate the practice of preparing simple financial reports with the final output being the Ora Food UMKM bookkeeping report in Gang Wirakaryan Sapen GK I No. 517C, Demangan Village, Gondokusuman District, Yogyakarta City, Yogyakarta Special Region. This service begins with training in creating simple cash flow. Here, the staff and students explain and give examples of how to record income or expenses. The training is divided into several stages, namely 1) Recording 2) Grouping 3) Elaboration and Elaboration and 4) Reporting. By implementing regular financial recording, it is hoped that partners can start managing the financial management of their business well. The implementation of community services through the financial management assistance program for Ora Food MSME partners can be carried out well and the results can improve the ability to make simple financial reports for Ora Food MSME owners. Keywords: financial reports; MSMEs; basic accounting; financial management.